Pyridine-Containing Polyhydroxyalkylation-Based Polymers for Use in Vanadium Redox Flow Batteries - Stonawski, Julian; Schroeder, Melanie; Gordes, Janett; Junginger, Frieder; Hager, Linus; Lauf, Pascal; Ikhsan, Muhammad Mara; Henkensmeier, Dirk; Thiele, Simon; Kerres, Jochen (ACS Applied Energy Materials, 2024)
In this work, a class of polymers with pendant pyridine moieties and variable p-terphenyl (pTP) content was developed via superacid catalyzed polyhydroxyalkylation (PHA). High controllability of the copolymer composition was demonstrated, allowing for straightforward fine-tuning of the material properties. Low levels of p-terphenyl were used to obtain materials with improved conductivities of up to 83 mS cm-1 in 3 M H2SO4, allowing the efficient application at high current densities. Increasing the p-terphenyl content significantly improved the selectivities up to 1.88 × 1013 S s m-3, resulting in optimized materials for low current density applications. A single cell equipped with BP-pTP10-Py exhibited an energy efficiency (EE) of 76.7% at a current density of 200 mA cm-2 (vs 73.7% for the commercial reference FAPQ330). At lower current density (50 mA cm-2), the single cells equipped with BP-pTP20-Py and BP-pTP35-Py showed the highest EE of 92.3% (vs 90.9% for the FAPQ330). Ex situ stability tests in 1.6 M V(V)/2 M H2SO4 proved high chemical stability with no changes in the NMR spectra and similar V(IV) contents in the stability solution as the reference FAPQ330. In addition, long-term in situ tests revealed no evidence of performance degradation for the single cell equipped with BP-pTP20-Py.
CRIS-Team Scopus Importer:2024-12-06
Keywords: improved selectivity; ion-selective membrane; Polyhydroxyalkylation; pyridine-containing; vanadium redox flow battery